Multi-Tier Targeting of Social Assistance : The Role of Intergovernmental Transfers - Alderman, Harold (Washington, DC: World Bank, 2014)
Albania provides a small amount of social assistance to nearly 20 percent of its population through a system that allows some community discretion in determining distribution. This study investigates how well this social assistance program is targeted to the poor. Relative to other safety net programs in low-income countries, social assistance in Albania is fairly well targeted. Nevertheless, the system is hampered by the absence of a clear, objective criterion to determine the size of the grants from the central government to communes as well as limited information that could be used to implement this criterion. Substantial gains in targeting could be achieved if the central government better allocated transfers to local governments, even holding local targeting at base levels.